Congenital adrenal hyperplasia with an ovarian adrenal rest tumor: a case report - Aydın Buyruk, Betül; Yorulmaz, Göknur; Değer, Ayşe Nur; Kebapçı, Medine Nur (The European Research Journal, 2020)
Adrenal rest tumors (ART) are extra-adrenal findings of adrenal tissue. Testicular adrenal rest tumors (TART) are widespread in males with congenital adrenal hyperplasia (CAH). Ovarian adrenal rest tumours (OART), which form in females with CAH, are less commonly seen. Reports in literature of OART are extemely rare. The case is here presented of a 43-year-old female who was diagnosed at the age of 15 years with CAH and underwent bilateral adrenalectomy at the age of 37. On presentation at our clinic, 4×2 cm mass was determined on the right adnexa in the advanced tests and a right-side salpingo-oopherectomy was performed. The pathology examination reported heterotopic adrenal cortical tissue. Routine ovarian imaging in females with CAH is not indicated. Although OART are rarely seen, they should be kept in mind and these patients should be evaluated radiologically together with laboratory tests.